Maria Merian: World-Traveling Entomologist - Magruder, Kerry (My University, 2015)
Maria Merian (1647-1717), skilled in both art and natural history, studied the relationships between flowers and insects. She conducted research in gardens and museums, produced detailed sketches and beautiful paintings, and even bred insects to aid in her entomological investigations. This OER explores the role of Merian in the development of entomology.
Keywords: History of Science; Galileo's World; Women in Science; Women's Studies.; entomology